Building Future-Ready Healthcare Systems Through Digital Literacy Training - Firmansyah; Ashari, Muhammad Rizki; Syam, Sadli (Indonesian Scientific Publication, 2025)
Digital literacy is a critical competency for healthcare professionals in delivering safe, effective, and patient-centered care. This narrative review examines global disparities in digital literacy training among healthcare workers, with a focus on identifying educational gaps, systemic and personal barriers, and innovative strategies for skill development. Literature was sourced from PubMed, Scopus, and Google Scholar, using predefined keywords targeting digital competency in clinical and educational contexts. Findings reveal significant disparities across healthcare professions and regions, with physicians generally showing higher proficiency than nurses and allied health workers. Systemic challenges such as limited ICT infrastructure, inadequate curricula, and weak institutional support are prevalent, particularly in low-resource settings. On a personal level, technophobia, low confidence, and concerns over workload hinder technology adoption. Innovative educational models—including simulation-based training, interactive e-learning, and problem-based learning—demonstrated positive outcomes in enhancing digital skills. However, their success is strongly tied to local infrastructure, faculty readiness, and socio-cultural factors. The review concludes that integrating digital literacy into healthcare education, investing in infrastructure, and promoting continuous professional development are essential to prepare future-ready health systems. Standardized measures and long-term outcome evaluations are recommended to assess the effectiveness of training interventions. Strengthening digital competencies is not merely a technical upgrade but a strategic imperative for resilient, equitable, and technology-enabled healthcare delivery..